(untitled) (Patan Prospective Journal, 2025)
This article analyzes the ongoing gender disparity in leadership roles within political, local government, corporate, and educational fields in Nepal. Utilizing secondary data from UN Women, government statistics, academic research, and journalistic analyses (2023 2025), the paper outlines present representation trends, pinpoints structural and socio cultural obstacles including patriarchy, gendered labor distribution, political party gate keeping, tokenism, and examines policy and programmatic solutions. The paper concludes with recommendations based on soft evidence to enhance meaningful female leadership beyond gains driven by quotas. The recent studies reveal advancement in representation at certain levels, yet there is still a predominance of women in deputy/support positions and a lack of representation at executive tiers. The representation trends in Nepal within political, local government, corporate, and educational leadership show a notable underrepresentation of women, underscoring the necessity for a thorough examination of the structural and cultural obstacles that hinder their progress to senior leadership roles. The major obstacles consist of deep-rooted patriarchal values, limited access to resources and networks, and inadequate support for balancing work and personal life, all of which lead to ongoing gender inequalities in leadership positions. To tackle these issues, it is crucial to suggest policy and program initiatives grounded in evidence that focus on attaining significant gender-balanced leadership. The examples of such measures include establishing quotas for female leaders, offering mentorship initiatives, and cultivating inclusive work environments that emphasize gender equality. By focusing on these essential aspects, Nepal can strive to build a more equitable leadership framework that represents the varied voices and experiences of its citizens.